Routine of Reading the Qur'an Related to Cognitive Function in Students of Muhammadiyah 01 Medan High School - Mulya Hasibuan, Firza; Yunafri, Andri (Buletin Farmatera, 2025)
Abstract: The Qur'an is the word of Allah Subhanahu Wa Ta'ala, which was revealed to the Prophet Muhammad (peace and blessings of Allaah be upon him) to be conveyed to mankind, especially to the people of the Prophet, as a guide for the life of Muslims in the world. The habit of reading the Qur'an is a continuous intellectual activity, which is worship. The purpose of this study is to find out the relationship between the routine reading of the Qur'an and the ability of cognitive function, especially in intellectual intelligence. This study is a comparative analytical research of 2 unpaired groups. The research design used is a true experimental design with post post-test only control group design. The research subjects totalled 40 people who were selected by the purposive sampling method. The analysis data used an independent t-test. Based on the results of the Independent Sample T-Test, a significance value (p-value) of 0.000 (0.05) was obtained.. The sample that regularly read the Qur'an for 1 month had a superior IQ score of 9 people (23%), a high average of 10 people (25%), and an average of 1 person (2.50%). Meanwhile, those who do not regularly read the Qur'an for 1 month have an average IQ score of 17 people (42.50%), and a low average of 3 people (7%). There is a significant influence on cognitive function, especially intellectual intelligence, from reading the Qur'an regularly for 1 month.